Prognostic Significance of Double-Expresser Status in Diffuse Large B-cell Lymphoma: Insights from a Tertiary Care Cancer Centre in India - Vijay, Smrthi; Arundhathi Vasudevan, Jayasudha; Nair, Rekha Appukuttan; Narayanan, Geetha; K.M., Jagathnath Krishna; Jacob,Priya Mary (Asian Pacific Journal of Cancer Care, 2024)
Background: Diffuse large B-cell lymphoma (DLBCL) is characterized by the proliferation of medium to large B lymphoid cells with a diffuse histopathologic growth pattern. The presence of the double-expresser (DE) phenotype, defined by co-expression of MYC and BCL2 proteins via immunohistochemistry (IHC), has been associated with inferior survival in DLBCL. This study aimed to assess the prevalence of DE status in DLBCL and evaluate its prognostic value. Methods: A retrospective analysis was conducted in a tertiary care cancer centre, focusing on all DLBCL, NOS cases diagnosed in 2012. MYC and BCL2 protein expression was determined using IHC. The prognostic significance of double-expressers was evaluated by comparing the progression-free survival (PFS) and overall survival (OS) between double-expressers and non-double expressers, employing appropriate statistical methods. Data were analyzed using SPSS version 11, and survival probabilities were estimated using the Kaplan-Meier method. The log-rank test was employed to assess differences in survival among various prognostic factors. Prognostic factors were further evaluated using univariate and multivariate Cox-regression models. A P-value < 0.05 was considered statistically significant. Results: DE lymphoma accounted for 22.2% (n=18) of all DLBCL, NOS cases. DE status was associated with significantly shorter PFS (P-value = 0.049) and OS (P-value = 0.015). Conclusion: The presence of DE status is indicative of poor prognosis in DLBCL, NOS. Assessment of MYC and BCL2 protein expression via IHC provides a rapid and cost-effective approach to risk-stratify DLBCL patients at the time of diagnosis.